2012
DOI: 10.1177/0020764012463298
|View full text |Cite
|
Sign up to set email alerts
|

Tendency towards stigmatization of families of a person with autistic spectrum disorders

Abstract: Anti-stigma programmes are important especially bearing in mind that participants who self-evaluated as having the least knowledge about ASD demonstrated the highest tendency towards stigmatizing the parents of a person suffering from ASD, and those of lower education demonstrated the highest tendency towards stigmatizing the family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
0
27
0
1
Order By: Relevance
“…Some studies suggest increased knowledge about ASD is associated with reduced stigmatising beliefs and attitudes (Milačić-Vidojević, Gligorović, & Dragojević, 2014;Obeid et al, 2015), and that autism training may improve knowledge and decrease stigmatising attitudes (Obeid et al, 2015;Tilahun et al, 2017). Similarly, parents of children with ASD found it easier to resist felt stigma when equipped with sufficient medical knowledge (Farrugia, 2009).…”
Section: Literacy In Mental Health and Typical Child Developmental Trmentioning
confidence: 99%
“…Some studies suggest increased knowledge about ASD is associated with reduced stigmatising beliefs and attitudes (Milačić-Vidojević, Gligorović, & Dragojević, 2014;Obeid et al, 2015), and that autism training may improve knowledge and decrease stigmatising attitudes (Obeid et al, 2015;Tilahun et al, 2017). Similarly, parents of children with ASD found it easier to resist felt stigma when equipped with sufficient medical knowledge (Farrugia, 2009).…”
Section: Literacy In Mental Health and Typical Child Developmental Trmentioning
confidence: 99%
“…While some affected by the condition lead independent and fulfilling lives, others suffer serious disabling consequences as a result of having autism [35,37]. It is possible that, at least in some cases, secondary disabilities may emerge as a result of inadequate care, stigma, and isolation that those affected may experience, both in LMICs (e.g., [2,38,39]) and HICs (e.g., [3•, 40]). …”
Section: Emergence Of Disability and Its Impactmentioning
confidence: 99%
“…Because cases of ASD are rarely exactly the same, there is a tendency for society to have conflicting ideas and perceptions of what autism is (Huws and Jones, 2010;Scior, 2011). This leads to stereotypes that are not only inaccurate, but also promote a stigma against them and their families (Milačić-Vidojević et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A way to reduce this stigma is to foster empathy among neurotypical people (that is, those not afflicted with a developmental disability) towards those with ASD. This becomes more imperative, considering that those who are unfamiliar with or know less about ASD have been found to be more likely to perpetuate the stigmatization (Milačić-Vidojević et al, 2014). Moreover, studies have found that increased empathy towards those in stigmatized groups can improve perceptions against those groups (Batson et al, 1997) and even motivate to help those (Batson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%